Allele and haplotype frequencies for HLA-DQ in Iranian celiac disease patients - Rostami-Nejad, Mohammad (Baishideng Publishing Group Inc, 2014)
AIM: To assess the distribution of human leukocyte antigen (HLA)-DQ2 and -DQ8 in Iranian celiac disease (CD) patients and compare them to healthy Iranian controls. METHODS: To predict the HLA-DQA1 and -DQB1 genes, we used six previously reported HLA-tagging single nucleotide polymorphism to determine HLA genotypes in 59 Iranian patients with ‘biopsy-confirmed’ CD and in 151 healthy Iranian individuals. To test the transferability of the method, 50 cases and controls were also typed using a commercial kit that identifies individual carriers of DQ2, DQ7 and DQ8 alleles. RESULTS: In this pilot study 97% of CD cases (n = 57) and 58% of controls (n = 87) were carriers of HLA-DQ2 and/or HLA-DQ8 heterodimers, either in the homozygous or heterozygous state. The HLA-DQ pattern of these 57 CD patients: heterozygous DQ2.2 (n = 14) and homozygous DQ2.2 (n = 1), heterozygous DQ2.5 (n = 33) and homozygous DQ2.5 (n = 8), heterozygous DQ8 (n = 13) and homozygous DQ8 (n = 2). Two CD patients were negative for both DQ2 and DQ8 (3%). CONCLUSION: The prevalence of DQ8 in our CD population was higher than that reported in other populations (25.4%). As reported in other populations, our results underline the primary importance of HLA-DQ alleles in the Iranian population’s susceptibility to CD.